Liberalisation of International Trade - The Case of Asymmetric Countries - Kosiec, Krzysztof (Central European Journal of Economic Modelling and Econometrics, 2016)
The aim of this paper is to analyse the welfare consequences of the processes of liberalisation of trade between asymmetric states in terms of the various sizes and effectiveness of their economies and the type of international exchange. These characteristics ultimately define the distribution of benefits from the liberalisation of international trade. When it is inter-industry or vertical intra-industry and barriers in trade are smaller than the difference in the effectiveness of the economies, the trade liberalisation undoubtedly contributes to improved social welfare, regardless of the level of effectiveness and the size of the economy. In the situation, however, of horizontal intra-industry trade, changes in the welfares of asymmetric countries, caused by their progressing trade liberalisation, depend on the sizes and effectiveness of their economies. The welfare of society in either a very big and ineffective or in a small and very ineffective country could even decrease in such a situation. This is the case when the increase in consumers’ surplus is not sufficient to compensate for the decreasing profits of firms.